Tetrasubstituted 1,3-enynes by gold-catalyzed direct C(sp2)-H alkynylation of acceptor-substituted enamines - Han, Chunyu; Tian, Xianhai; Zhang, Huili; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2021)
A gold-catalyzed synthesis of tetrasubstituted 1,3-enynes from hypervalent iodine(III) reagents and activated alkenes is reported. This reaction involves an in situ formed alkynyl Au(III) species and a subsequent direct C(sp2)-H functionalization of alkenes, offering 26 enynes in 62-92% yield with excellent functional group tolerance.